¿Cuál es el destino de los países abundantes en recursos minerales? Nueva evidencia sobre la relación entre recursos naturales, instituciones y crecimiento económico - Perla, Cecilia (2004)
Economies that have large endowments of natural resources, especially the ones thatrely on oil and minerals, are ofien regarded as unlikely to develop, or even seen as cursedby nature. It is said that the mineral rents, which could be used to trigger a growthprocess, have in practice several negative effects that by and large counteract their potentialpositive contributions. Nevertheless, it seems that these results are sensitive tothe measures of resource abundance that are used, and mineral resource abundancemight not be necessarily growth retarding. This study will evaluate if the arguments touphold that mineral rich countries are dwmed to low economic growth are strong andsound by testing a number of robustness checks on the standard models of resourcesand growth. We test if there are any specification bias in the model proposed i n pa rticularof omitted variables- and if the resource curse thesis remains robust whenusing other measures of resource abundance, and when testing specifically for a mineralrecOurce curse.